Using the UTAUT2 model to explain teacher acceptance of work performance assessment system - Artika Arista; Bahtiar Saleh Abbas (International Journal of Evaluation and Research in Education (IJERE), 2022)
An organization needs qualified and experienced human resources. Performance appraisals are required to determine the effectiveness of their work. A performance appraisal system has already been created to objectively evaluate the work of teachers, principals, and teachers given additional tasks, and to provide instructions for developing the teaching profession, principals, and teachers given additional tasks. The goal of this study was to apply the unified theory of acceptance and use of technology 2 (UTAUT2) to explain why teachers accept the performance appraisal method. With the help of SmartPLS 3.2.8 software, a partial least square structural equation model (PLS-SEM) was used to analyze the data. The results showed that behavioral intention (BI) to utilize the system is influenced by performance expectancy (PE), social influence (SI), facilitating conditions (FC), and habit (HT). The findings also revealed that system use behavior (UB) is influenced by facilitating conditions (FC), habit (HT), and behavioral intention (BI). To increase the system's adoption, the studies suggest focusing on enhancing the system's ease of use and minimizing the system's flow complexity.